2017
DOI: 10.1021/acs.jpca.7b06359
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Freezing of Carbon Nanotubes: A Model System for Pore Condensation and Freezing in the Atmosphere

Abstract: Heterogeneous ice nucleation is an important mechanism for cloud formation in the upper troposphere. Recently, pores on atmospheric particles have been proposed to play a significant role in ice nucleation. To understand how ice nucleation occurs in idealized pores, we characterized the immersion freezing activity of various sizes of carbon nanotubes. Carbon nanotubes are used both as a model for pores and proxy for soot particles. We determined that carbon nanotubes with inner diameters between 2 and 3 nm exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…However, why the earlier work indicated that BC is an effective ice‐nucleating material (Murray et al, 2012; Phillips et al, 2008, 2013) is unclear, and it may be that combustion of some fuels under some conditions can produce BC that is strongly ice active. As mentioned above, elemental carbon in some forms has been shown to nucleate ice effectively (Alstadt et al, 2017; Bai et al, 2019; Whale, Rosillo‐Lopez, et al, 2015), but it remains unclear if this highly ice‐active form of BC is atmospherically important. Nevertheless, we have shown that BC generated on Bonfire Night from a range of fuels and combustion conditions has a very low ice‐nucleating activity and does not significantly enhance the INP population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, why the earlier work indicated that BC is an effective ice‐nucleating material (Murray et al, 2012; Phillips et al, 2008, 2013) is unclear, and it may be that combustion of some fuels under some conditions can produce BC that is strongly ice active. As mentioned above, elemental carbon in some forms has been shown to nucleate ice effectively (Alstadt et al, 2017; Bai et al, 2019; Whale, Rosillo‐Lopez, et al, 2015), but it remains unclear if this highly ice‐active form of BC is atmospherically important. Nevertheless, we have shown that BC generated on Bonfire Night from a range of fuels and combustion conditions has a very low ice‐nucleating activity and does not significantly enhance the INP population.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that BC nucleates ice when immersed in (or at least in the presence of) supercooled droplets (DeMott, 1990; Diehl & Mitra, 1998; Fornea et al, 2009; Gorbunov et al, 2001; Kireeva et al, 2009; Popovicheva et al, 2008; Wright et al, 2013). In addition, carbon‐based materials including graphene oxides and carbon nanotubes nucleate ice, which shows that carbon‐rich materials have the potential to nucleate ice (Alstadt et al, 2017; Bai et al, 2019; Whale, Rosillo‐Lopez, et al, 2015). Murray et al (2012) parameterized data from DeMott (1990), who used soot from an oxygen‐deficient acetylene burner, and Diehl and Mitra (1998), who used a kerosene burner, by calculating the ice‐active site surface density, n s ( T ), of BC, and concluded that BC may be a very important INP type globally.…”
Section: Introductionmentioning
confidence: 99%
“…Immersion freezing data were taken using an environmental chamber described in detail in Alstadt et al 60 Briefly, 2 μL droplets of 0.02 wt. % of iron oxide powder in UHPLC-MS water (Fisher Scientific) were pipetted onto silanized slides (Hampton Research).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Additionally, BET analysis with nitrogen gas was performed on the ASAP 2020 Automated Surface Area and Porosimetry System to determine the surface area of each sample. 44 Immersion freezing data were taken using an environmental chamber described in detail by Alstadt et al 45 Briefly, 2 μL droplets (∼7 mm diameter) of 0.02 wt % alumina in ultrapure water (Millipore Q, 18.2 Ω•cm 2 ) were pipetted onto siliconized slides (Hampton Research). From the average diameter (50 μm) observed with SEM, approximately 100 alumina particles are within each drop.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%